'The medicine from China has rapid effects' - Hsu, E (Taylor and Francis, 2002)
Traditional Chinese Medicine (TCM) involves both biomedical and traditional medical training, which makes well-trained TCM doctors inexpensive health care providers for primary health care. The Tanzanian Ministry of Health and Ministry of Commerce recognised this potential, and in the mid-1990s issued short-term licences for private TCM enterprises. In Dar es Salaam, some of these practices experiences a period of considerable growth, but by the year 2000 a degree of ambivalence if not resentment existed against Chinese medical doctors who were accused of unlawfully using biomedical medication, and the government refused to issue further licences. In addition, some 'doctors' had insufficient training or minimal clinical experience (though I also met some notable exceptions). This article asks why Tanzanian patients turn to the Chinese for medical treatment, and who patients know about Chinese medicine and medication. One of the chief findings is that the Swahili term dawa ya Kichina is vague, which allows patients to transfer their positive experiences with Chinese biomedical doctors during the period of socialist orientation onto the current, entrepreneurial TCM doctors. Dawa ya Kichina is often considered a rapidly effective 'advanced' 'traditional' medicine; its ready-made patent formulas, which make it look 'scientific' and 'modern', are easy to consume; and its entrepreneurial set-up has several advantages over the bureaucratic structures of 'hospital medicine'. Chinese anti-malarials, artesiminin derivatives, reduce malarial fevers within hours, and though, strictly speaking, they are biomedical drugs, they are indeed dawa ya Kichina. Moreover, patients of TCM doctors sometimes experience rapid recovery mostly due to skilled integration of biomedical and Chinese medical treatment. Further research is recommended to investigate the primary health care potential of such integrated Chinese and biomedical treatment.